Prevalence and Associated Factors of Problematic Smartphone Use During the COVID-19 Pandemic: A Bangladeshi Study - Hosen I; al Mamun F; Sikder MT; Abbasi AZ; Zou L; Guo T; Mamun MA (Dove Medical Press, 2021)
Ismail Hosen,1,2 Firoj al Mamun,1,2 Md Tajuddin Sikder,2 Amir Zaib Abbasi,3 Liye Zou,4 Tianyou Guo,4 Mohammed A Mamun1,2 1CHINTA Research Bangladesh, Dhaka, Bangladesh; 2Department of Public Health and Informatics, Jahangirnagar University, Dhaka, Bangladesh; 3Department of Management Sciences, Shaheed Zulfikar Ali Bhutto Institute of Science and Technology, Islamabad, Pakistan; 4Exercise Psychophysiology Laboratory, Institute of KEEP Collaborative Innovation, School of Psychology, Shenzhen University, Shenzhen, People's Republic of ChinaCorrespondence: Tianyou Guo; Mohammed A Mamun Email gtyou168@126.com; mamunphi46@gmail.comBackground: Problematic smartphone use (PSU) has been increasing hastily in recent decades, and it has become inseparable during the COVID-19 pandemic, especially among the students who are at risk of problematic smartphone use. Therefore, the present study aimed to investigate the prevalence and associated factors of PSU during the COVID-19 pandemic among the Bangladeshi students.Methods: A total of 601 Bangladeshi students were recruited through an online-based cross-sectional survey that was conducted between October 7 and November 2, 2020. The survey collected information related to socio-demographics, behavioral health, internet use behaviors, depression, anxiety, and PSU. Independent samples t-test and one-way ANOVA were performed to present the relationship between the studied variables and PSU. Multiple linear regression analysis was also used for investigating the explanatory power of the predictive models for PSU.Results: Surprisingly, about 86.9% of the students scored to be problematic smartphone users (≥ 21 out of a total 36 based on the Smartphone Application-Based Addiction Scale). In addition, medical students, engaging in a relationship, performing less physical activity, longer duration of internet use, some sorts of internet use purpose (eg, messaging, watching videos, using social media), depression, and anxiety were significantly associated with higher scores of PSU. After adjusting all the studied variables, the final model explained a 31.3% variance predicting PSU.Conclusion: The present study is one of the first approaches to assess the prevalence of PSU among the Bangladeshi students during the COVID-19 pandemic, whereas the addiction level was superfluous (and this may be due to more online engagement related to the pandemic). Thus, the study recommended strategies or policies related to the students' risk-reducing and healthy use of smartphones.Keywords: Bangladeshi student, Bangladesh, smartphone, problematic smartphone use, smartphone addiction in Bangladesh, smartphone overuse, technological addiction